Development of an on-animal separation-based sensor for monitoring drug metabolism in freely roaming sheep1. Issue 11 (7th June 2015) - Scott, David E.; Willis, Sean D.; Gabbert, Seth; Johnson, David; Naylor, Erik; Janle, Elsa M.; Krichevsky, Janice E.; Lunte, Craig E.; Lunte, Susan M.
<x xml:space="preserve">Abstract</x> Lab-on-a-sheep: on-animal sensor using microdialysis coupled to microchip electrophoresis with electrochemical detection.